A multi-site study examining the usability of a virtual reality game designed to improve retention of sterile catheterization skills in nursing students. (April 2021) - Breitkreuz, Karen R.; Kardong-Edgren, Suzan; Gilbert, Gregory E.; DeBlieck, Connie; Maske, Mariam; Hallock, Christy; Lanzara, Susan; Parrish, Kathryn; Rossler, Kelly; Turkelson, Carman; Ellertson, Anthony; Brown, Kimberly N.; et al.
Ausability study of aVirtual Reality Sterile Urinary Catheter Insertion Game (VR SUCIG) was conducted to understand user needs in regards to this game. Background: Learning and retention ofpsychomotor skills in health care is essential tosafe clinical practice . Bauman suggests games are most useful when they are part of a layered-learning approach; in other words, they support various forms of learning and serve as cognitive aids (Bauman et al., 2014 ). Intervention: TheVR Sterile Urinary Catheter Insertion Game (VRSUCIG) was created by nurses and a computer gaming developer to provide nursing students with a cost-effective way to practice sterile catheter insertion skills in a systematic, evidence-based manner. A usability study and user reaction survey were conducted to gain a deep understanding of user's needs. Methods: Three hundred nursing students, from 9 US nursing schools participated. Participants played the VR SUCIG and completed theSystem Usability Scale (SUS) and aUser Reaction Survey (URS). Results: The SUS for the 2nd generation of the VR SUCIG was 57, or medium usability. The URS demonstrated the game motivated them to keep practicing. The VR SUCIG promotedrepetitive practice of the skill and visually accentuated the concept of sterility. Conclusions. User reactions indicate that nursing students were eager and excited to utilize this technology. Usability scores indicate further refinement of technology is needed.